(untitled) (Journal of Engineering, 2006)
Conformal projection is one of the most important aspects that geodesy dealing with. The determination of the scale factors in the meridian, the parallel and projected geodesic directions are the final result of the conformal projection. Methods for determining the scale factors in the meridian and the parallel directions have a quite sufficient accuracy. While methods for determining the projected geodesic have different accuracy and computation complicity. This research adopts a modified method for computing the exact value of scale factor in geodesic direction. In this method the scale factor is obtained by determining the true and projected distances of the geodetic line. In the traditional methods for determining the projected distance it is usual to use the 1/3 Simpson’s rule in the computations while the modified method the 3/8 Simpson’s rule is used. Computations and mathematical tests were carried out to obtain the scale factors using the traditional methods and comparison was made with modified method. By applying the developed method and the traditional methods to calculate the scale factor, it was found that the modified method is more accurate and the projected distances can be obtained exactly.